(untitled) (Journal of Universal Science Research, 2023)
This article analyzes the methodological aspects of evaluating the efficiency of innovative management of enterprises based on the systematic analysis of the efficiency indicators of industrial enterprises. The article also presents the factors affecting the efficiency of innovative management of industrial enterprises, based on grouping them according to the spheres of influence, a scientific proposal and practical recommendations aimed at increasing the efficiency of innovative management of industrial enterprises have been developed.